Discipline and punish: The birth of the prison - Foucault, Michel 1926-1984 (London Penguin Books, 1979)
In the Middle Ages there were gaols and dungeons, but punishment was for the most part a spectacle. The economic changes and growing popular dissent of the 18th century made necessary a more systematic control over the individual members of society, and this in effect meant a change from punishment, which chastised the body, to reform, which touched the soul. Foucault shows the development of the Western system of prisons, police organizations, administrative and legal hierarchies for social control - and the growth of disciplinary society as a whole. He also reveals that between school, factories, barracks and hospitals all share a common organization, in which it is possible to control the use of an individual's time and space hour by hour.